2022
DOI: 10.3390/ani12050608
|View full text |Cite
|
Sign up to set email alerts
|

Handling and Physiological Aspects of the Dual-Purpose Water Buffalo Production System in the Mexican Humid Tropics

Abstract: The purpose of this paper is to describe the characteristics of the dual-purpose water buffalo production based on the Mexican production system as a model in tropical wetlands. It includes a broad literature review emphasizing the most recent and specialized publications examining key findings to improve our understanding in the performance of the buffalo species (Bubalus bubalis). The complementary topics addressed include reproductive management, parturition, the dam–calf bond, milking routines, and models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 96 publications
0
27
0
Order By: Relevance
“…These factors help explain why they decided to incorporate an emerging species such as the river buffalo into their operations and integrate a certain technology level to potentiate their capacities. We found that one of these PUs recently went through a generational change that favored the continuity of these activities and facilitated continuous improvement in its buffalo-raising activity [22,23].…”
Section: Social Aspectsmentioning
confidence: 99%
See 4 more Smart Citations
“…These factors help explain why they decided to incorporate an emerging species such as the river buffalo into their operations and integrate a certain technology level to potentiate their capacities. We found that one of these PUs recently went through a generational change that favored the continuity of these activities and facilitated continuous improvement in its buffalo-raising activity [22,23].…”
Section: Social Aspectsmentioning
confidence: 99%
“…According to these figures, the DPBPS form a specific stratum within the framework of dual-purpose production units in Mexico's tropical wetlands. The larger production scale also reflects the producers' high socioeconomic level, increasing the probability that their operations will be viable financially and technically [20,23].…”
Section: Land Tenure and The Surface Area Availablementioning
confidence: 99%
See 3 more Smart Citations